Drosophila Argonaute 1 and its miRNA biogenesis partners are required for oocyte formation and germline cell division - Azzam, G; Smibert, P; Lai, E; Liu, J (2012)
Argonaute 1 (Ago1) is a member of the Argonaute/PIWI protein family involved in small RNA-mediated gene regulation. In . Drosophila, Ago1 plays a specific role in microRNA (miRNA) biogenesis and function. Previous studies have demonstrated that Ago1 regulates the fate of germline stem cells. However, the function of Ago1 in other aspects of oogenesis is still elusive. Here we report the function of Ago1 in developing egg chambers. We find that Ago1 protein is enriched in the oocytes and is also highly expressed in the cytoplasm of follicle cells. Clonal analysis of multiple . ago1 mutant alleles shows that many mutant egg chambers contain only 8 nurse cells without an oocyte which is phenocopied in . dicer-1, . pasha and . drosha mutants. Our results suggest that Ago1 and its miRNA biogenesis partners play a role in oocyte determination and germline cell division in . Drosophila. © 2012.